Družbeni učinki urbanega kmetijstva - Halilović, Nela (Georitem, 2019)
The book presents urban agriculture as an innovative and effective tool for achieving wider social effects regarding the participation in decision-making processes, social inclusion, and sustainable urban development. Despite the many social and economic benefits, this kind of agriculture has still not gotten the proper support at the international and national political levels. In Slovenia, there are no clear guidelines and standards for its promotion, protection and management. This is why one of the purposes of this book is to encourage the first step towards bridging the gap between the national and local levels. The overview of good urban agriculture practices in the countries of Central and Eastern Europe and North America attests that the wider social effects are most often ensured by community, social, educational, and therapeutic gardens that bring together many diverse stakeholders. The book illustrates how urban agriculture, when designed in a collaborative and inclusive manner, can result in improved public services, boost active citizenship, and contribute to a better urban structure and image.